Effectiveness of Using Hotspot Facilities The Internet as a Learning Resource for TJKT Students at SMK Negeri 1 Kupang - Sardi, Fidelis; Enstein, jhon; Taku, Khatrin J. (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The purpose of this study was to determine the effectiveness of using internet hotspot facilities as one of the learning resources for TJKT students at SMK Negeri 1 Kupang from the perspective of students and to provide solutions to the obstacles faced by TJKT students in using internet hotspot facilities as one of the learning resources at SMK Negeri 1 Kupang. In this study, the approach used was a quantitative approach. By using a quantitative descriptive method, reviewed from the form of data and analysis techniques, it is included in the quantitative approach, because the data obtained is in the form of numbers and is resolved using statistical methods. The test results using the Sigmon application showed variations in connection quality at various hotspot points. Although in general the download and upload speeds are sufficient for browsing and downloading files. This can be influenced by several factors, such as distance from the router, number of users, and signal interference. The average speed of the hotspot speed test in class XI TJKT 4, the average value of the download speed is 63.89 mbps, for uploading 61.14 mbps. And for class XI TJKT 5, the average download speed is 138.92 mbps, for uploading 103.35 mbps. For speed measurement using the SIGMON speed test application, the average value of the download speed is 47.21 mbps, for uploading 40.19 mbps. The results of the study indicate that the use of internet hotspot facilities at SMK Negeri 1 Kupang is very effective in increasing student access to learning resources. It is proven that there is a significant relationship between the use of internet hotspot facilities and increasing student access to learning resources at SMK Negeri 1 Kupang.